Intercultural Competence in Language Teaching: German after English A pilot study of the classes 4–6 in Poznan/Poland - Zuzok, Nadja (Glottodidactica, 2010)
The following essay is about teaching German after English and the intercultural traces that can be found in German teaching and learning after having been learned English. The current polish situation makes this topic relevant, as German is taught as second foreign language. The present study wants to investigate which influence this learning German after English has when speaking of intercultural competence.